Observation of the upper atmosphere physics at Asuka Station by the 30th Japanese Antarctic Research Expedition in 1989 - Akira Yukimatu (National Institute of Polar Research, 1992)
This paper describes observations of the upper atmosphere physics at Asuka Station from January 1 to December 24,1989,carried out by the 30th Japanese Antarctic Research Expedition (JARE-30). In JARE-30 one research member of the upper atmosphere physics has been wintering at Asuka Station, and several instruments were newly installed so as to observe auroral phenomena in conjunction with Syowa Station, Iceland observations, and scientific satellites. Characteristics of the JARE-30's observations at Asuka Station are as follows : 1) The observation of CNA with a 30-MHz riometer has been made throughout the year. 2) A fixed direction and a tracking photometers were newly installed, and spatial and temporal developments of aurora photo emissions in various wave lengths were observed. 3) An all sky camera used in JARE-28 was re-installed. 4) An all sky SIT-TV camera was newly installed so as to observe auroral motions with high time resolution. 5) A digital data recorder was installed for the auroral photometric data. 6) Z-component of a ULF induction magnetometer which had been in trouble was recovered, so we could observe the three components of both a fluxgate magnetometer and the induction magnetometer. 7) In 1989,the solar activity was very high and there were many interesting geophysical events, and auroral phenomena.